Solution process of graphene-induced ohmic contact between the metal and AlGaN/GaN for hemts application - Tran Viet Cuong,; Huynh Vo, Anh Hao; Nguyen, The Duy; Dinh, Duc Anh; Tran, Trung Tin; Tran, Trung Nghia (Vietnam Journal of Science and Technology, 2024)
This work demonstrates an AlGaN/GaN high electron mobility transistor (HEMT) with Cr/Graphene ohmic contacts constructed without heat treatment. The Cr/Graphene ohmic contact was fabricated using a spray-coated graphene nanoflakes solution and electron-beam-evaporated Cr. This method does not require a high-temperature annealing step in conventional Ti/Al/Ni/Au ohmic contact. It is suggested that the Cr/graphene combination acts similarly to a doped n-type semiconductor in contact with AlGaN/GaN heterostructures, enabling carrier transport to the AlGaN layer. The investigated Au/Cr/ Graphene/AlGaN/GaN HEMT device exhibits ohmic drain characteristics in the range of -4 V to 4 V of drain-source voltage with a calculated contact resistance density of 2.5 mΩcm2. Our results have important implications for the fabrication and manufacturing of AlGaN/GaN-based microelectronic and optoelectronic devices/sensors of the future.